2010
DOI: 10.1080/00224540903365463
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Organizational Support and Turnover Intention: The Mediating Effects of Personal Sacrifice and Job Fit

Abstract: This study examines the mediating role of job fit on the relationship between perceived supervisor support (PSS) and perceived organizational support (POS), and the mediating role of personal sacrifice on the relationship between POS and turnover intention. We use structural equation modeling (SEM) with a data set consisting of a sample of 346 individuals in a manufacturing firm to test our proposed model of PSS, POS, and turnover intention. Consistent with prior literature, our hypothesized model confirms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
146
0
23

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(200 citation statements)
references
References 49 publications
(104 reference statements)
17
146
0
23
Order By: Relevance
“…Organizational commitment denotes an emotional attachment and identification with an organization. Organizational citizenship behaviors embody non-required and uncompensated actions such as punctuality, attendance, aiding coworkers, voluntarily assuming ad-hoc tasks and assisting management in implementing new tasks (Dawley et al, 2010). However, over the next 20 years it is likely that the idea of developing emotional ties to the organization will not be enough, and organizations will no longer have the luxury of being concerned with employees performing extra-role behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational commitment denotes an emotional attachment and identification with an organization. Organizational citizenship behaviors embody non-required and uncompensated actions such as punctuality, attendance, aiding coworkers, voluntarily assuming ad-hoc tasks and assisting management in implementing new tasks (Dawley et al, 2010). However, over the next 20 years it is likely that the idea of developing emotional ties to the organization will not be enough, and organizations will no longer have the luxury of being concerned with employees performing extra-role behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion and conclusion are provided in the final section. turnover decisions, it is important to consider the mechanisms through which perceived organizational justice acts on turnover intention (Dawley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard some researchers (Dawley, Houghton, & Bucklew, 2010;Iverson & Buttigieg, 1999;Lynn, 2004;McGee & Ford, 1987;Somers, 1995;Vandenberghe & Panaccio, 2012) have identified continuance commitment to have two sub-dimensions. This concept of continuance commitment is based on the scarcity of alternatives and a sacrifice of management role such as seniority which he might not get if he quits the job.…”
Section: Organizational Commitment (Oc)mentioning
confidence: 99%
“…All studies indicated a negative association between supervisor support and TI. Employees who perceived that their supervisors cared about them and valued their contributions reported lower levels of TI [2,11,19]. …”
mentioning
confidence: 99%